Water quality index as a simple indicator of aquaculture effects on aquatic bodies - Simoes, Fabiano dos Santos; Moreira, Altair Benedito [UNESP]; Bisinoti, Marcia Cristina [UNESP]; Gimenez, Sonia M. Nobre; Santos Yabe, Maria Josefa (Elsevier B.V., 2008)
This paper proposes a water quality index (WQI) to subsidize management actions in the Medio Paranapanema Watershed in São Paulo State, Brazil, as a simple pollution indicator for aquaculture activity. Water quality of the Macuco and Queixada rivers was investigated for 2 years (from May 2003 to May 2005). The index proposed in this work is composed of three measurable environmental parameters-turbidity, total phosphorus and dissolved oxygen. Concentrations of these three variables were normalized on a scale from 0 to 100 and translated into statements of water quality (excellent, good, regular, fair and poor). The index was applied to seventeen monitoring points in the aquatic bodies described above and compared to others, one being that used by the Environmental Protection Agency of United States and proposed for the National Sanitation Foundation, other employing minimal index and the last one considering the minimum operator concept. The results show that the degradation in this watershed from aquaculture activity can be easily inferred with this index, which is more restricted than the others routinely used to infer water quality. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: water quality index (WQI); aquaculture activity; Pollution; aquatic bodies